Effects of Vertically and Horizontally Orientated Plyometric Training on Physical Performance: A Meta-Analytical Comparison - Garcia-Hermoso, A (Springer Science and Business Media Deutschland GmbH, 2021)
Background: In accordance with the principle of training specificity, adaptations to vertically or horizontally orientated plyometric training (VPT, HPT) directly transfer to athletic tasks that are carried out in the same direction as they are performed. Objectives: The objective of this systematic review and meta-analysis was to determine the relative effect of VPT and HPT on both vertical and horizontal measures of physical performance. Data Sources: Google Scholar, CrossRef, Microsoft Academic, PubMed, Web of Science, Scopus. Study Eligibility Criteria: To qualify for inclusion in the meta-analysis, studies must have included a plyometric training intervention that compared jumps executed in a vertical direction [i.e. countermovement jump (CMJ)] to jumps executed in a horizontal direction (i.e. standing horizontal jump). Study Appraisal and Synthesis Methods: We used the inverse-variance random effects model for meta-analyses. Effect sizes, calculated from measures of horizontally or vertically orientated performance, were represented by the standardised mean difference and presented alongside 95% confidence intervals (CI). Results: For between-group analysis on horizontal outcomes, there was a moderate, significant effect size (ES) in favour of HPT (0.65 [95% CI 0.12, 1.18], Z = 2.41 [p = 0.02]). For the analysis on vertical outcomes, there was a trivial, non-significant difference between VPT and HPT (− 0.04 [95% CI − 0.33, 0.24], Z = 0.0.29 [p = 0.77]). Within-group analysis showed HPT to be superior to VPT across horizontally- (1.05 [0.38, 1.72] vs. 0.84 [0.37, 1.31]) and vertically-orientated (0.74 [0.08, 1.40] vs. 0.72 [0.02, 1.43]) performance measures. For horizontally-orientated outcomes, single-factor moderator analyses showed that longer programmes (> 7 weeks), more sessions (> 12) and combined bilateral and unilateral training were most effective, favouring HPT in each case. In vertically orientated outcomes, these same variables showed only trivial differences between HBT and VBT. Conclusions: HPT is at least as effective as VPT at enhancing vertical performance but is superior at enhancing horizontal performance. This means that HPT might be a more efficient method for enhancing multi-vector performance for sport. © 2020, Springer Nature Switzerland AG.